Experience of antihomotoxica in the complex treatment of acute odontogenic periostitis jaws (LLC "Endo Press", 2020)
In the present study, we investigated the effectiveness of drugs with different mechanisms of action in the treatment of patients with acute odontogenic periostitis of jaws. The best effect is observed in the case of appointment of a complex antibacterial and antihomotoxic medications in the postoperative period. The use of antimicrobial drugs only suppress the local immunity in the early stages of treatment.